Simultaneous Preconcentration and Determination of Trace Amount of Lead and Copper in Water Samples by Flame Atomic Absorption Spectrometry - ZAVVAR MOUSAVI, H.; SHIRKHANLOO, H. (Asian Journal of Chemistry, 2010)
In the present paper, a simple and sensitive method for simultaneous preconcentration and determination of lead and copper by flame atomic absorption spectrometry was developed. This method was based on solid phase extraction of lead and copper with 1-nitroso-2-naphthol-3,6-disulfonic acid chelate on naphthalene column. After preconcentration stage, the column was eluted by 5 mL of 1.2 mol L-1 nitric acid solution and metal ions directly determined by flame atomic absorption spectrometry. The effect of different variables such as pH, sample volume, amount of chelate, flow rate and eluent solution on the recovery of the analyte was investigated. The detection limits were 0.7 and 0.5 μg L-1 for lead and copper, respectively. The relative standard deviations of the determinations for analyte ions were below 4 %. This procedure was applied to the determination of lead and copper in water samples. The results demonstrated that the procedure can be applied for analysis of waters with satisfactory accuracy.